The Protective Effect of Apocynin on Cyclosporine A‐Induced Hypertension and Nephrotoxicity in Rats. Issue 9 (September 2015) - Ciarcia, Roberto; Damiano, Sara; Florio, Alessia; Spagnuolo, Manuela; Zacchia, Enza; Squillacioti, Caterina; Mirabella, Nicola; Florio, Salvatore; Pagnini, Ugo; Garofano, Tiziana; Polito, Maria Sole; Capasso, Giovambattista; et al.
ABSTRACT Cyclosporine A (CsA) is the prototype of immunosuppressant drugs that has provided new perspectives in human and veterinary medicine to prevent organ transplant rejection and to treat certain autoimmune diseases and dermatologic diseases. Unfortunately, the treatment with CSA is often limited by severe adverse effects such as hypertension and nephrotoxicity. Some data suggest that reactive oxygen species (ROS) and the oxidative stress play an important role in its pathogenesis, in particular the superoxide (O2−) that is the most powerful free radical generated by nicotinamide adenine dinucleotide phosphate (NADPH) oxidase present mainly in the kidney. The present study has been designed to investigate the role of Apocynin a selective inhibitor of NADPH oxidase activity on cyclosporine‐induced adverse effect. In this study, we have evaluated the effect of CsA, used alone or in association with Apocynin on blood pressure (BP), on glomerular filtration rate (GFR), on absoluted fluid reabsorption (Jv) in proximal tubule (PT), on O2− concentration, and on nitric oxide (NO) production. We have demonstrated that CsA administration increases superoxide concentration in the aorta, decreases the NO concentration, reduces GFR and the Jv in PT, and induces a significant increase in BP. Moreover, we have shown that Apocynin treatment restores these hemodynamic alterations, as well as NO and superoxide productions. In conclusion, the reported data indicate that CsA induced nephrotoxicity and hypertension are related to NADPH oxidase activity, in fact Apocynin protects the kidney function and BP from toxic effects induced by CsA through the inhibition of NADPH oxidase activity. J. Cell. Biochem. 116: 1848–1856, 2015. © 2015 Wiley Periodicals, Inc.